2007
DOI: 10.1007/s00425-007-0621-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeting and localization of wound-inducible leucine aminopeptidase A in tomato leaves

Abstract: The constitutive and wound-inducible leucine aminopeptidases (LAP-N and LAP-A, respectively) of tomato encode 60-kDa proteins with 5-kDa presequences that resemble chloroplast-targeting peptides. Cell fractionation studies and immunoblot analyses of chloroplast and total proteins have suggested a dual location of the mature LAP-A proteins in the cytosol and the plastids. In this study, the subcellular localization of tomato LAPs was further investigated using in vitro chloroplast-targeting assays and immunocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…However, due to the differences in their subcellular localizations, the peptidase/chaperone substrates of the Arabidopsis LAP1, which is located in the cytosol (33), are likely to be distinct from those of the plastid-localized LAP-A, LAP-N, and LAP2 (6,18). In addition, it is possible that the stress-induced LAP-A has a different set of peptidase/chaperone substrates from LAP-N and LAP2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the differences in their subcellular localizations, the peptidase/chaperone substrates of the Arabidopsis LAP1, which is located in the cytosol (33), are likely to be distinct from those of the plastid-localized LAP-A, LAP-N, and LAP2 (6,18). In addition, it is possible that the stress-induced LAP-A has a different set of peptidase/chaperone substrates from LAP-N and LAP2.…”
Section: Discussionmentioning
confidence: 99%
“…LAP-A resides within the plastid (18), which is a dynamic compartment subject to many cellular stresses during development and biotic/abiotic stresses that can result in protein damage and aggregation. In order to prevent the accumulation of misfolded proteins, cells express a wide range of molecular chaperones (19).…”
mentioning
confidence: 99%
“…Finally, exogenous application of JA to LapA-SI and wildtype plants showed that JA did not restore wound signaling in LapA-SI lines, indicating that LAP-A acted downstream of JA biosynthesis. Collectively, these data and the facts that LAP-A and Prosystemin are localized to distinct cellular compartments indicated that LAP-A is unlikely to influence the biogenesis of systemin (Narvá ez-Vá squez and Ryan, 2004;Narvá ez-Vá squez et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The LAP-A1 and LAP-A2 mature proteins are 99% identical and reside within the chloroplast (Matsui et al, 2006;Narvá ez-Vá squez et al, 2007). LAP-A1 and LAP-A2 are 77% identical with LAP-N, which is expressed at low levels constitutively (Tu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the M1 family carry a canonical HEXXH motif in their active site, whereas the M17 family members lack this motif and require two metal ions per monomer for activity [31]. LAPs have diverse subcellular localizations; initially found in the cytosol, they have been subsequently encountered in chloroplasts [32], on bacterial surfaces [33], or teguments of parasitic helminths [34]. Moreover, in Escherichia coli LAPs bind DNA [35], while they are amongst secreted proteins in other bacteria such as Mycoplasma [33].…”
Section: Introductionmentioning
confidence: 99%